Co-production of blaNDM-1 and blaOXA-23 in multiresistant clinical isolates of Acinetobacter baumannii from Brazil (Research, Society and Development, 2022)
Acinetobacter baumannii is a common and dangerous non-fermenting gram-negative bacillus due to its various and increasing resistance mechanisms. Therefore, the objective of the work was to describe four NDM-1 -producing Acinetobacter isolates from Natal, northeastern Brazil. These four isolates were identified as Acinetobacter baumannii by MALDI-TOF. All isolates were characterized by antimicrobial susceptibility testing, with resistance to all β-lactams including carbapenems and positive for the synergy test with Ethylenediaminetetraacetic acid. PCR analysis was also performed for blaNDM-1, blaVIM-1, blaIMP-1, blaOXA-23, blaOXA-24/40, blaOXA-51, blaOXA-58, and blaOXA-143 genes and showed positive for the blaNDM-1 and blaOXA-23 genes in all isolates and this result was confirmed by sequencing. This is the first case of Acinetobacter baumannii strains harboring blaNDM-1 gene isolated from northeastern Brazil. This description emphasizes the need for new prevention and control strategies of the dissemination of NDM-1-producing Acinetobacter, which are associated with a high mortality rate.